Small and Medium Enterprises towards Indonesia’s Significant Role in G20 and Economic Sustainable Development - Susilo, Ghina Fitri Ariesta (Asian Administration and Management Review, 2019)
This study is a qualitative desk research. The research’s goal is to enhance the understanding of important influence of Indonesia Small and Medium Enterprises (SMEs) among G20 member countries. Using ten design principles for industrial policy by Rodrik (2004), this research identified how SMEs could be a big influence for Indonesia’s economic sustainable development. A survey by OECD informed that Indonesia is in the fourth position for its Growth Domestic Product (GDP) and economic development among G20 member countries. The SMEs' development contains with Rodrik’s model, one of ten designs is to give incentive programs to subsidize SMEs, so they can improve their productivity and opportunities. Government of Indonesia has given incentives since 2007 to help Indonesia’s SMEs activities. The contribution SMEs to GDP has increased from 57.84% to 60.34% in the last five years per 2016. Those facts lead to the conclusion that in achieving sustainable economic development, Indonesia should constantly determine to push the growth of SMEs. Some lacks are still happened. But, by giving more innovative programs and implement supportive policies, the role of Indonesia in G20 will be stronger and the long-term effect will strengthen Indonesia’s SMEs.